2020
DOI: 10.21203/rs.3.rs-24953/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

"Who is Watching the Watchdog?": Ethical Perspectives of Sharing Health-related Data for Precision Medicine in Singapore

Abstract: Background: We aimed to examine the ethical concerns Singaporeans have about sharing health-data for precision medicine (PM) and identify suggestions for governance strategies. Just as Asian genomes are under-represented in PM, the views of Asian populations about the risks and benefits of data sharing are under-represented in prior attitudinal research. Methods: We conducted seven focus groups with 62 participants in Singapore from May to July 2019. They were conducted in three languages (English, Mandarin an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…It may be difficult to implement recommendation 4 which calls for the oversight committee to consider the consequences of data sharing with respect to fairness and relative financial disadvantage among Singaporeans. Review committees are typically not in a position to accurately predict future downstream consequences of research (Rogers and Ballantyne, 2009). However, those involved in the NPM should be attuned to the distribution of the benefits of PM and work towards achieving affordable healthcare for Singaporeans, addressing inequity and caring for the most vulnerable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It may be difficult to implement recommendation 4 which calls for the oversight committee to consider the consequences of data sharing with respect to fairness and relative financial disadvantage among Singaporeans. Review committees are typically not in a position to accurately predict future downstream consequences of research (Rogers and Ballantyne, 2009). However, those involved in the NPM should be attuned to the distribution of the benefits of PM and work towards achieving affordable healthcare for Singaporeans, addressing inequity and caring for the most vulnerable.…”
Section: Discussionmentioning
confidence: 99%
“…Prior qualitative research (Lysaght et al, 2020) and a recent survey of Singaporean's views about health data sharing (Lysaght et al, 2021), found that broad versus specific models of consent were less important to respondents than other considerations such as the use and users of the data: similar evaluations may also have informed the jury's focus. The reasons for this de-emphasize on individual consent (for each instance of data sharing) will need to be explored in future research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation